GulfCARE Trial Characterizes AHF Patients in the Middle East - Vinall, Phil (MD Conference Express, 2014)
The results of the Gulf Acute Heart Failure Registry [GulfCARE; NCT01467973] showed that patients in the Middle East who are diagnosed with acute heart failure are younger than their Western counterparts, have a higher rate of diabetes mellitus, and lower rate of atrial fibrillation. Mortality rates are close to those reported in Western studies; however, this should be re-evaluated in light of the younger age of Middle Eastern patients.